Formulation and Characteristic Effervescent Tablets of Water Gourd (Lagenaria siceraria) With Variation Sodium Bicarbonate Concentration - Silvia Triana Pradini; Nadya Ambarwati; Fikria Marfuatin Nur; Nur Rachmawati (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Lagenaria siceraria, commonly known as bottle gourd, is a plant from the Cucurbitaceae family that contains bioactive compounds such as flavonoids, vitamin C, and saponins with potential antioxidant properties. This study aimed to develop effervescent tablets from Lagenaria siceraria using varying concentrations of sodium bicarbonate based on a Full Factorial Design method. The independent variable was the concentration of sodium bicarbonate, while the dependent variables included flow properties, angle of repose, moisture content, organoleptic characteristics, weight and size uniformity, hardness, friability, and dissolution time. Results showed that flow rate ranged from 5.1 ± 0.007 to 5.49 ± 0.025 seconds (p = 0.004), angle of repose from 25.21 ± 0.42 to 25.5 ± 0.024 degrees (p = 0.026), and moisture content from 3.08 ± 0.09 to 4.71 ± 0.027% (p = 0.080). The tablets met the requirements for weight and size uniformity. Tablet hardness ranged from 6.44 ± 1.42 to 7.75 ± 0.56 kP (p = 0.016), friability from 0.16 to 0.81% (p = 0.055), and dissolution time from 1.82 ± 0.02 to 1.96 ± 0.01 minutes (p = 0.047). In conclusion, variations in sodium bicarbonate concentration significantly affected flow properties, angle of repose, hardness, and dissolution time, but had no significant effect on moisture content and friability. Keywords: Lagenaria siceraria; sodium bicarbonate; effervescent tablet